Political Transformation of Indonesian Tourism Law: A Critical Study of Sustainable Tourism Policy - Nengah Sujana; Feri Irawan Widiyatmoko; Made Sinta Syaharani Sujana (Fakultas Hukum, Universitas Warmadewa, 2025)
Legal political transformation is a key element in creating sustainable tourism in Indonesia. Based on Law No. 10/2009 on Tourism and Bali Province Regional Regulation No. 5/2020, this study analyzes the implementation of sustainability principles in legal policies, which include environmental preservation, social justice, and economic welfare. Although sustainability principles have been implemented, challenges such as lack of policy harmonization, weak supervision, and low involvement of local communities remain. A comparative approach with other countries, such as Bhutan and New Zealand, shows the importance of collaboration between central and local governments. This research recommends updating the legal framework, using technology for monitoring, and strengthening the participation of indigenous communities, in order to realize economically, ecologically, and socio-culturally sustainable tourism, with a local wisdom-based approach.